Geographical variation of emergency hospital admissions for ambulatory care sensitive conditions in older adults in Ireland 2012–2016 - Fiona Boland; Emma Wallace; Tom Fahey; Mary E Walsh; Mark H Ebell; Sinead Cronin (BMJ Open, 2021)
Objective Ambulatory care sensitive (ACS) conditions are those for which intensified primary care management could potentially prevent emergency admissions. This study aimed to quantify geographical variation in emergency admissions with ACS conditions in older adults and explore factors influencing variation.Design Repeated cross-sectional study.Setting 34 public hospitals in the Ireland.Participants Adults aged ≥65 years hospitalised for seven ACS conditions between 2012 and 2016 (chronic obstructive pulmonary disease, congestive heart failure (CHF), diabetes, angina, pyelonephritis/urinary tract infections (UTIs), dehydration and pneumonia).Primary outcome measure Age and sex standardised emergency admission rates (SARs) per 1000 older adults.Analysis Age and sex SARs were calculated for 21 geographical areas. Extremal quotients and systematic components of variance (SCV) quantified variation. Spatial regression analyses was conducted for SARs with unemployment, urban population proportion, hospital turnover, supply of general practitioners (GPs), and supply of hospital-based specialists as explanatory variables.Results Over time, an increase in UTI/pyelonephritis SARs was seen while SARs for angina and CHF decreased. Geographic variation was moderate overall and high for dehydration and angina (SCV=11.7–50.0). For all conditions combined, multivariable analysis showed lower urban population (adjusted coefficient: −2.2 (−3.4 to −0.9, p<0.01)), lower GP supply (adjusted coefficient: −5.5 (−8.2 to −2.9, p<0.01)) and higher geriatrician supply (adjusted coefficient: 3.7 (0.5 to 6.9, p=0.02)) were associated with higher SARs.Conclusions Future research should evaluate methods of preventing admissions for ACS conditions among older adults, including how resources are allocated at a local level.